2020
DOI: 10.21203/rs.3.rs-31151/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Covid-19 on General Surgical Practice in India

Abstract: Introduction: The Coronavirus disease—2019 (COVID‐19) pandemic is a global health crisis and surgeons are at increased occupational risk of contracting COVID‐19. The impact of the disease on prevalent general surgical practice is uncertain and continues to evolve.Aims/Objectives: To study the impact of COVID-19 on general surgical practice in India and the future implications of the pandemic.Methods: A survey questionnaire was designed and electronically circulated one month after India entered a national lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…A survey conducted in India during the nationwide lockdown by Manik Nasta et al . reported a higher rate of deferring elective surgery by general surgeons (77%)[ 16 ] in comparison to this study. This hints towards the rising trend of the resumption of elective surgical care post lockdown.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…A survey conducted in India during the nationwide lockdown by Manik Nasta et al . reported a higher rate of deferring elective surgery by general surgeons (77%)[ 16 ] in comparison to this study. This hints towards the rising trend of the resumption of elective surgical care post lockdown.…”
Section: Discussioncontrasting
confidence: 60%
“…There have been reports of widespread shortage and re-use of PPE to circumvent the shortage. [ 21 ] This study shows that approximately 66%–86% of surgeons are using the recommended PPE as compared to that of the previous studies conducted during the lockdown,[ 16 ] which reported 34%–56.9% usage of PPE. Around 95% of the surgeons are using respirators, such as N95 or respirators, that offer a higher level of protection.…”
Section: Discussionmentioning
confidence: 64%
“…Lockdown measures in India have also been associated with decreased access to health care and exacerbation of common non-communicable or chronic conditions 28 including cancer, 29 diabetes, 30 tuberculosis, 31 and others. 32 , 33 Longer-term studies remain important to determine the effect of these changes on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2 The pandemic has affected the hospital functioning and patient care. [1][2][3][4] Doctors and health care workers are the frontline workers in the battle against ongoing pandemic. We conducted this survey to study the impact of COVID-19 pandemic on doctors' clinical practice.…”
Section: Introductionmentioning
confidence: 99%